Can mental imagery functional magnetic resonance imaging predict recovery in patients with disorders of consciousness? - Vogel, Dominik; Markl, Alexandra; Yu, Tao; Kotchoubey, Boris; Lang, Simone; Müller, Friedemann (Archives of physical medicine and rehabilitation, 2013)
Objective - To determine the potential prognostic value of using functional magnetic resonance imaging (fMRI) to identify patients with disorders of consciousness, who show potential for recovery. - Design - Observational study. - Setting - Unit for acute rehabilitation care. - Participants - Patients (N=22) in a vegetative state (VS; n=10) and minimally conscious state (MCS; n=12) during the first 200 days after the initial incident. - Interventions - Not applicable. - Main Outcome Measure - Further course on the Coma Recovery Scale-Revised. - Results - Participants performed a mental imagery fMRI paradigm. They were asked to alternately imagine playing tennis and navigating through their home. In 14 of the 22 examined patients (VS, n=5; MCS, n=9), a significant activation of the regions of interest (ROIs) of the mental imagery paradigm could be found. All 5 patients with activation of a significant blood oxygen level dependent signal, who were in a VS at the time of the fMRI examination, reached at least an MCS at the end of the observation period. In contrast, 5 participants in a VS who failed to show activation in ROIs, did not (sensitivity 100%, specificity 100%). Six of 9 patients in an MCS with activation in ROIs emerged from an MCS. Of 3 patients in an MCS who did not show activation, 2 patients stayed in an MCS and 1 patient emerged from the MCS (sensitivity 85%, specificity 40%). - Conclusions - The fMRI paradigm mental imagery displays a high concordance with the further clinical course of patients in a VS. All 5 patients in a VS who showed significant activation of ROIs had a favorable further course until the end of the observation period. We therefore propose the term “functional minimally conscious state” for these patients. They may benefit from rehabilitation treatment. In cases where no significant activation was seen, the method has no prognostic value. Prediction of the clinical course of patients in an MCS by fMRI was considerably less accurate than in patients in a VS.
Gesehen am 03.03.2022